Policy Analysis Of Islamic Religious Education In Public Schools And Universities - Lilik Kholisotin; Tobroni, Tobroni (Jurnal Hadratul Madaniyah, 2025)
This study analyzes the policy of Islamic Religious Education (PAI) in Indonesian public schools and universities within the framework of national education. Using a qualitative library research approach, data were collected from constitutional documents, educational regulations, academic works, and scholarly discussions. The findings show that PAI is not only a curricular requirement but also a strategic instrument for shaping moral character, strengthening national identity, and fostering religious moderation in a pluralistic society. Despite strong legal foundations, the implementation of PAI faces challenges from globalization, secularization, and the spread of radical content through digital media. However, opportunities also emerge through technological integration and innovative pedagogical approaches that can enhance inclusiveness, tolerance, and critical engagement. The study concludes that strengthening PAI policies requires adaptive curricula, digitally competent educators, and collaborative efforts among stakeholders to ensure that Islamic education contributes meaningfully to the development of a faithful, moderate, and socially responsible generation.